Widely tunable multiwavelength Brillouin-erbium fiber laser with triple Brillouin-shift wavelength spacing - Al-Mansoori, M.H.; Al-Sheriyani, A.; Younis, M.a.a.; Mahdi, M.A. (Elsevier, 2018)
In this paper, we demonstrate a widely tunable multiwavelength Brillouin-erbium fiber laser (MBEFL) having a wavelength spacing of 0.25 nm (triple Brillouin-shift wavelength spacing). The proposed laser structure overcomes the need for Brillouin pump wavelength to be closed to the self-lasing cavity modes region. The laser exhibits a wide tuning range of 40 nm (from 1530 nm to 1570 nm) at Brillouin pump and 980 nm pump powers of 25 mW and 350 mW, respectively. Four stable output channels are produced within this wavelength range with all the channels having a peak output power greater than 1.58 mW. The laser has the potential to be used as a multiwavelength laser source for dense wavelength division multiplexing communication.